1986
DOI: 10.1084/jem.163.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Accessory cell-T lymphocyte interactions. Antigen-dependent and -independent clustering.

Abstract: Previous work documented the capacity of dendritic cells (DC) to stimulate primary immune responses and to physically cluster with the responding lymphocytes. Rapid cell-cell aggregation assays were used here to study the interaction of DC and other types of APC with T lymphocytes. Graded doses of APC were sedimented with T cells that had been primed to alloantigens, soluble proteins, or lectin, and then labeled with carboxyfluorescein diacetate. The number of clustered T cells was measured after 10 min at 4 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(102 citation statements)
references
References 14 publications
2
99
1
Order By: Relevance
“…Thus migration of DC from the blood to the spleen is regulated by T cells. Although we initially thought that this might be due to direct DC-T cell clustering, analogous to that studied in vitro (30) and implicated in vivo (38), elsewhere we present evidence that is contrary to this idea (17). In particular, we have found that the DC are initially localized within the red pulp of the spleen but that later, and only after a period of what appears to be active migration, they enter the white pulp.…”
Section: Discussioncontrasting
confidence: 49%
“…Thus migration of DC from the blood to the spleen is regulated by T cells. Although we initially thought that this might be due to direct DC-T cell clustering, analogous to that studied in vitro (30) and implicated in vivo (38), elsewhere we present evidence that is contrary to this idea (17). In particular, we have found that the DC are initially localized within the red pulp of the spleen but that later, and only after a period of what appears to be active migration, they enter the white pulp.…”
Section: Discussioncontrasting
confidence: 49%
“…Memory T cells were prepared by resting the blasts for three or more days in the absence of exogenous IL-2 or alloantigen (19) . The blasts and memory populations were >70% allospecific, as assessed in rapid DC-T binding assays (28 Mixtures of accessory-cell depleted B and T lymphocytes were obtained by passing spleen suspensions over Sephadex G10 (17) . 4 X 10 lymphocytes were cultured in 16-mm-diam wells for 4 d with antigen (2 X 106 SRBC; or 10,ug/ml TNP-KLH) and graded doses of DC (17).…”
Section: T Cells and T Cell Proliferationmentioning
confidence: 99%
“…They are the principal stimulators of primary immune responses [13,26,35,38,39]. In studies of lymphoid DC as potent stimulators of the MLR in mice, Steinman and Whitmer [7] showed that a ratio of just one DC to 50-250 T cells induced a maximal reaction. Wong et al [42] demonstrated that DC were reproducibly the most potent stimulators of T cell responses on a per cell basis when compared with macrophages even when higher levels of MHC molecules were induced on the surface of macrophages with IFN-γ [36].…”
mentioning
confidence: 99%
“…Dendritic cells (DC) are efficient stimulators of both allogeneic and syngeneic mixed lymphocyte reaction, MLR [7]. They are the principal stimulators of primary immune responses [13,26,35,38,39].…”
mentioning
confidence: 99%